2018
DOI: 10.1139/cjas-2017-0083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lysine level on the content and fatty acid composition of intramuscular fat in late-stage finishing pigs

Abstract: 22This study was conducted to investigate how dietary lysine level affects the intramuscular 23 fat (IMF) content and fatty acid (FA) composition in late-stage finishing pigs. Nine crossbred 24 barrows (94.4 ± 6.7 kg BW) were randomly allotted to three treatment groups (n = 3). Three corn 25 and soybean-meal based diets were formulated to meet the NRC (2012) requirements for various 26 nutrients except for lysine, whose concentrations were 0.43%, 0.71%, and 0.98% (as-fed basis) 27for Diets 1 (lysine-deficient)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Nevertheless, the highest omega-6 values of linoleic acid and arachidonic acid associated with dietary mixtures containing high lysine levels may also reveal a boosting effect attributable to high lysine levels. Similar patterns were reported in pigs fed low and high dietary lysine than the optimum one, where LA, LNA and total PUFA percentages rose significantly ( p ≤ 0.014) with increased dietary lysine levels [ 48 ]. Increased linseed oil intake, similarly, resulted in higher de novo ω-3 PUFA synthesis and, as a result, increased total PUFA levels in chicken meat [ 45 , 60 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Nevertheless, the highest omega-6 values of linoleic acid and arachidonic acid associated with dietary mixtures containing high lysine levels may also reveal a boosting effect attributable to high lysine levels. Similar patterns were reported in pigs fed low and high dietary lysine than the optimum one, where LA, LNA and total PUFA percentages rose significantly ( p ≤ 0.014) with increased dietary lysine levels [ 48 ]. Increased linseed oil intake, similarly, resulted in higher de novo ω-3 PUFA synthesis and, as a result, increased total PUFA levels in chicken meat [ 45 , 60 ].…”
Section: Discussionsupporting
confidence: 76%
“…In the current study, stearic acid is the only fully saturated fatty acid increased by increasing dietary levels of linseed and/or lysine. An inverse relationship was found between the percentages of stearic acid, total SFA and the amount of dietary lysine in pigs [ 48 ]. The addition of linseed oil was associated with a decrease in SFA in chicken meat [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, lower dietary lysine levels have been previously correlated with a higher proportion of monounsaturated fatty acids, the LD IMF content did not differ substantially between the groups ( 17 ). This argues against the predominant effect of lysine, as it has been reported that the IMF content of the muscle increases with decreasing dietary lysine levels ( 43 ).…”
Section: Discussionmentioning
confidence: 95%
“…The use of low protein and low amino acid feeds (LP) has recently emerged as one of the best strategies to reduce the environmental release of N compounds from pig farms. In many experiments, LP diets have been found to increase fat cover thickness and intramuscular fat 1214 . Greater fat cover thickness reduces the water losses during ripening, and this would exert positive effects on the final quality of the product 15,16 .…”
Section: Introductionmentioning
confidence: 99%